2004
DOI: 10.1097/00002820-200409000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Intervention for Watchful Waiting in Prostate Cancer

Abstract: Watchful waiting is a reasonable alternative to treatment for some older men with localized prostate cancer, but it inevitably brings uncertainty. This study tested the effectiveness of the watchful waiting intervention (WWI) in helping men cognitively reframe and manage the uncertainty of watchful waiting. Based on Mishel's Reconceptualized Uncertainty in Illness Theory (Image. 1990; 256-262), the WWI was tested with a convenience sample of 41 men. Experimental subjects received 5 weekly intervention calls fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
133
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 30 publications
3
133
1
3
Order By: Relevance
“…These aspects may explain the levels of uncertainty in the study participants. Uncertainty has been found among patients with prostate cancer who are undergoing watchful waiting [34,35] or among survivors of breast cancer [15]. Among the latter group, the uncertainty levels (mean = 57.08, SD=10.14) were lower than the ones of our study participants [15].…”
Section: Discussioncontrasting
confidence: 64%
“…These aspects may explain the levels of uncertainty in the study participants. Uncertainty has been found among patients with prostate cancer who are undergoing watchful waiting [34,35] or among survivors of breast cancer [15]. Among the latter group, the uncertainty levels (mean = 57.08, SD=10.14) were lower than the ones of our study participants [15].…”
Section: Discussioncontrasting
confidence: 64%
“…A small, prospective, randomized trial of 41 patients on a watchful-waiting protocol demonstrated that patients on the experimental (intervention) arm, who received 5 weekly calls from a nurse, had both an increase in quality of life (P 5 .01) and decreased confusion (P 5 .04) as measured on multiple validated questionnaires. 29 There are several limitations to the current study. There may be a self-selection bias on the part of these patients who are presenting to a referral center.…”
Section: Discussionmentioning
confidence: 92%
“…Recognition of the contribution of uncertainty to psychological distress in men with prostate cancer is not new. It is acknowledged to be particularly associated with watchful wait or active monitoring protocols (Wallace, 2003;Bailey et al, 2004) and reported to be present in survivors of the disease (Talcott, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Across all domains measured, men with psychological distress had greater unmet supportive care needs. Nurse-led interventions for uncertainty have been developed and evaluated (Mishel et al, 2002;Bailey et al, 2004), as have those for depression (McCorkle et al, 2007). Arguably, a clinical nurse specialist could deliver such interventions following the requisite training.…”
Section: Discussionmentioning
confidence: 99%